2021
DOI: 10.1038/s41467-021-25140-2
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast femtosecond pressure modulation of structure and exciton kinetics in 2D halide perovskites for enhanced light response and stability

Abstract: The carriers’ transportation between layers of two-dimensional (2D) perovskites is inhibited by dielectric confinement. Here, for the first time, we employ a femtosecond laser to introduce ultrafast shock pressure in the range of 0~15.45 GPa to reduce dielectric confinement by modulating the structure and exciton dynamics in a perovskite single crystal (PSCs), e.g. (F-PEA)2PbI4 (4-fluorophenethylammonium, F-PEA). The density functional theory (DFT) simulation and experimental results show that the inorganic fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 58 publications
(64 reference statements)
0
24
0
Order By: Relevance
“…Opposite trends of the lattice deformation depending on the laser power density might arise from the structural defects formed by the laser shock wave. 40 Upon laser irradiation, the g-C 3 N 4 NS surface was under a large out-of-plane compressive pressure along the direction of the g-C 3 N 4 film thickness, which also gave rise to lateral extension. 41 Thus, the laser pulse generated out-of-plane contraction and in-plane expansion in the g-C 3 N 4 NS film (laser power density ≤348.4 MW cm −2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Opposite trends of the lattice deformation depending on the laser power density might arise from the structural defects formed by the laser shock wave. 40 Upon laser irradiation, the g-C 3 N 4 NS surface was under a large out-of-plane compressive pressure along the direction of the g-C 3 N 4 film thickness, which also gave rise to lateral extension. 41 Thus, the laser pulse generated out-of-plane contraction and in-plane expansion in the g-C 3 N 4 NS film (laser power density ≤348.4 MW cm −2 ).…”
Section: Resultsmentioning
confidence: 99%
“…(j) DFT simulated band structure and density of states (DOS) without ultrafast pressure. Reprinted with permission from ref . Copyright 2021 Song et al, published by Springer Nature.…”
Section: Preparation and Engineering Methods And The Related Property...mentioning
confidence: 99%
“…Ablation in a gas environment is easier to control than that in a liquid environment, which is usually employed to process nanoproducts such as metals, metallic alloys, semiconductors, and polymers. For instance, Song et al, for the first time, introduced ultrafast shock pressure ranging from 0 to 15.45 GPa from a femtosecond laser, aiming at tailoring the atomic structures and exciton dynamics of (FPEA) 2 PbI 4 to reduce dielectric confinement (Figure g) . The results indicated that inorganic framework distortion led to a band gap decrease of 150 meV­(Figure j).…”
Section: Preparation and Engineering Methods And The Related Property...mentioning
confidence: 99%
See 1 more Smart Citation
“…Laser is a kind of coherent optical radiation based on the principle of stimulated emission amplification. The 2D perovskite material exhibits a strong photoluminescence spectrum and adjustable emission spectra due to material modification, which ensure its application in the laser field. …”
Section: Lasermentioning
confidence: 99%